2022
DOI: 10.1002/anie.202208216
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Zintl Compound In1−xGaxTe: Pure Acoustic Phonon Scattering and Dopant‐Induced Deformation Potential Reduction and Lattice Shrink

Abstract: We report a Zintl phase thermoelectric material, coarse grain-In 0.99 Ga 0.01 Te, achieving a ZT peak of 1.2 at 648 K and an average ZT = 0.8 in 300-650 K, which outperforms all the known InTe-based materials to date. The synergistic optimization of electronic property and phonon transport are achieved by the purification of grain boundary scattering, together with the Ga-doping-induced weak phonon-electron coupling, which enhances the carrier mobility and carrier concentration simultaneously and consequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…Figure f shows that the highest peak zT value at 725 K is 0.64, obtained in the In 0.99 Sn 0.01 Te sample, more than 50% higher than 0.41 at 725 K in the undoped sample. The peak zT of the In 0.99 Sn 0.01 Te sample in this study is comparable with those of many reported doped InTe polycrystalline samples ,, but lower than those of In 0.999 Pb 0.001 Te and In 0.99 Ga 0.01 Te samples.…”
Section: Resultssupporting
confidence: 90%
“…Figure f shows that the highest peak zT value at 725 K is 0.64, obtained in the In 0.99 Sn 0.01 Te sample, more than 50% higher than 0.41 at 725 K in the undoped sample. The peak zT of the In 0.99 Sn 0.01 Te sample in this study is comparable with those of many reported doped InTe polycrystalline samples ,, but lower than those of In 0.999 Pb 0.001 Te and In 0.99 Ga 0.01 Te samples.…”
Section: Resultssupporting
confidence: 90%
“…The representative frequency of 1.0 THz in SnTe is responsible for 90% of the cumulative κ L , indicating that the low-frequency phonon in SnTe dominates the thermal transport. This scenario further demonstrates that the Cd-induced low-frequency optical phonons and phonon softening significantly contribute to κ L reduction, and a similar phenomenon has also been observed in other TE compounds, such as InTe, 49 CsCu 4 Se 3 , 50 and YbFe 4 Sb 12 , 51 exhibiting ultralow lattice thermal conductivity.…”
Section: Resultssupporting
confidence: 75%
“…21 These results strongly manifest that sufficient κ L reduction can be realized in the solid solution of (SnTe) 1− x (MnCd 1− y Ge y Te 2 ) x by introducing abundant hierarchical nano/mesostructures and low-frequency optical modes to scatter phonons at all scales. ZT is proportional to the quality factor ( B ), which can be calculated with eqn (7): 49 where μ W is an n H -independent quantity, which can essentially quantify the number and mobility parameter ( μ 0 ) of conduction channels for charge carrier transport. 68 Consequently, the decoupling effect ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Thermoelectric materials play a very important role in applications such as waste heat energy conversion, , solid-state cooling, and power supplies . The conversion efficiency is mainly determined by the figure of merit zT ( zT = ( S 2 σ/κ) T , where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature). Zintl-phase compounds have been considered as promising thermoelectric materials due to their “phonon-glass electron-crystal” structure. The anion groups connected by covalent bonds in the crystal structure mainly play the role of carrier transport, while the cations that form ionic bonds with the anion groups mainly play the role of scattering phonons. Up to now, a series of Zintl compounds have been reported as promising thermoelectric materials, such as Yb 14 MnSb 11 , YbCd 2 Sb 2 , , Eu 2 ZnSb 2 , , CaZn 0.4 Ag 0.2 Sb, Ca 10 GdCdSb 9 , Ca 9 Zn 4+ x Sb 9 , KGaSb 4 , BaAg 2 Te 2 , etc .…”
Section: Introductionmentioning
confidence: 99%